รัฏฐาธิปัตย์กับพระพุทธศาสนา - อนนท์จารย์, ผศ.ดร.สุขพัฒน์ (วารสารศรีล้านช้างปริทรรศน์, 2015)
การก่อตัวเป็นรัฐจะต้องอาศัยประชาชนเป็นหลัก เช่นเดียวกับศาสนาการจะก่อตัวเป็นศาสนาได้จะต้องอาศัยศาสนิกชนเช่นกัน กล่าวคือ ประชาชนกลุ่มเดียวกันนี้เช่นกัน เพราะฉะนั้นทั้งศาสนาและรัฐต่างมีกลุ่มชนอย่างเดียวกัน ต่างฝ่ายจะต้องพึ่งพาและอาศัยอยู่ด้วยกัน เพราะมีประชาชนเป็นผู้ให้การยอมรับอย่างเดียวกัน จึงแยกออกจากกันไม่ได้ต่างฝ่ายต่างก็มีเอกภาพเช่นเดียวกัน ได้แก่ ฝ่ายอาณาจักรก็คือภาครัฐ เปรียบเสมือนกาย ฝ่ายศาสนจักรก็คือภาคศาสนา เปรียบเสมือนใจ ทั้งสองฝ่ายระหว่างกายกับใจต่างต้องอยู่ด้วยกัน ซึ่งแยกออกจากกันไม่ได้           จะเห็นได้ว่า ระหว่างรัฐกับศาสนาต่างก็มีภารกิจที่แตกต่างกัน บางกิจก็ทำร่วมกัน กล่าวคือ ภาครัฐก็จะให้การสนับสนุนคุ้มครองศาสนา เช่น การจัดสรรงบประมาณเพื่อสนับสนุนกิจการในด้านต่าง ๆ ในพระพุทธศาสนา ส่วนศาสนาก็ให้การอบรมสั่งสอนคนในภาครัฐให้เป็นคนดีมีคุณธรรม เป็นต้น หากคนในภาครัฐไม่ดีหรือขาดคุณธรรม ก็บ่งบอกถึงความไม่เอาใจใส่ในหน้าของฝ่ายศาสนจักร หรือฝ่ายศาสนาไม่ได้รับการคุ้มครองเท่าที่ควร จะเป็นการบ่งบอกถึงภาครัฐไม่ใส่ใจในหน้าที่เช่นกัน           เมื่อทั้งสองฝ่ายต่างทำหน้าที่แต่ละฝ่ายอย่างสมบูรณ์พร้อมแล้ว ความสมดุลยภาพทางสังคมก็จะเกิดขึ้น ความผาสุกของผู้คนในรัฐก็จะปรากฏ ความสงบสุขความเป็นระเบียบเรียบร้อยก็จะมี ปัญหาในด้านต่าง ๆ ก็จะไม่เกิดขึ้น ในทางตรงกันข้ามหากฝ่ายหนึ่งฝ่ายใดละเลยในหน้าที่ของตน ปัญหาก็จะเกิดตามมาทันใด ไม่ทางใดก็ทางหนึ่งอย่างแน่นอน           จากการเปลี่ยนแปลงไปทางสังคม ที่มีต่อค่านิยมการปกครอง ชาวไทยนิยมชมชอบระบบประชาธิปไตยเสียเป็นส่วนมาก ชุดความคิดจึงก่อเกิดระบบการปกครองคณะสงฆ์ขึ้นมา จากเดิมที่อาศัยเฉพาะพระธรรมวินัย มีพระราชบัญญัติคณะสงฆ์ ซึ่งภาครัฐเป็นผู้ออกพระราชบัญญัติฉบับนี้ขึ้นมา ก็เพื่อเป็นเครื่องมือในการปกครองคณะสงฆ์ จนกลายเป็นว่าภาครัฐได้เข้าปกครองคณะสงฆ์ คณะสงฆ์เองก็ยอมรับในสิ่งที่ภาครัฐได้ดำเนินการเช่นนั้น อย่างที่เป็นอยู่ในสถานการณ์ปัจจุบัน             The foundation of a state was surely dependent upon the people and the foundation of any religion was also the same because of its followers, who were known the same people in that state.  In fact, both the state and the Buddhist Authoritative Council were said to have the same people, and each of them was dependent upon and associated with each other because the same group of people became their acceptors. So, both of them were not separated from each other because of integrity. The state or the kingdom was said like the human body, and the religion’s authority was in comparison of the human mind. The body and the mind had to combine together and could not be separated.           There were distinct duties between the state and the Buddhist Authoritative Council but some duties were operated together. The state had its duty to support and protect the religion. For example, the budget was allotted by Thailand’s government to support and promote the Buddhist affairs whereas the state authorities were taught and trained to be good persons by the Buddhist monks. In case the state authorities were found without morality and virtue, it would be referred to the Buddhist Authoritative Council’s ignorance of duties. Conversely, if the Buddhist Authoritative Council were not protected as much as possible, the state was said to ignore its duties, as well.            Whenever duties of both sides were completed, in the state, social balance arose, well-being of people appeared, peace and orderliness existed, and no social problems occurred. Inversely, if duties of any side were ignored, certain problems would immediately arise somehow.           Regarding the social change to the country’s governance value, most of Thai people were in flavor of democracy. Such a mindset resorted to the Sangha administration. The Council of Buddhist monks in Thailand was distinctively said under the state control through the country’s Sangha Act, so-called the state instrument to govern the Council of Buddhist monks in Thailand, apart from the Doctrine and Discipline, appointed by the Buddha, the founder of Buddhism. It was that the state came into governing the council of Buddhist monks, who accepted what the state performed as seen at present.